1998
DOI: 10.1002/(sici)1096-8628(19980907)81:5<420::aid-ajmg11>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for linkage to psychosis and cerebral asymmetry (relative hand skill) on the X chromosome

Abstract: The hypothesis that psychosis arises as a part of the genetic diversity associated with the evolution of language generates the prediction that illness will be linked to a gene determining cerebral asymmetry, which, from the evidence of sex chromosome aneuploidies, is present in homologous form on the X and Y chromosomes. We investigated evidence of linkage to markers on the X chromosome in 1) 178 families multiply affected with schizophrenia or schizoaffective disorder with a series of 16 markers spanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
3
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 33 publications
7
47
3
1
Order By: Relevance
“…26 Very recently this QTL was confirmed 27 in a subset of left-handed male brothers from a previously collected sample cohort. 25 However, we found no evidence of this QTL in this genome scan. Given the amount of power present in our sample cohort, the characteristics of Klar's model, the NPL results and the robustness of two-point analysis against model misspecification, we can assume that if the monogenic models were correct, it would have been possible to detect this single locus.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…26 Very recently this QTL was confirmed 27 in a subset of left-handed male brothers from a previously collected sample cohort. 25 However, we found no evidence of this QTL in this genome scan. Given the amount of power present in our sample cohort, the characteristics of Klar's model, the NPL results and the robustness of two-point analysis against model misspecification, we can assume that if the monogenic models were correct, it would have been possible to detect this single locus.…”
Section: Discussioncontrasting
confidence: 68%
“…24,25 Association analysis between allele sharing of markers on the X-chromosome and a reduction of hand skill variance in left-handed brothers resulted in an LOD score of 2.8 for marker DXS990. 25 In this genome scan, no positive LOD scores were obtained for DXS990, thereby providing no evidence for the presence of a locus on the X-chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The retroviral sequence derived from a cDNA library from postmorte brain tissue of an individual with psychosis in a genomic region (Xq21.3). The Xq21.3 region has been tentatively linked to schizophrenia and schizoaffective disorder by Laval et al (1998). We identified two retroposons, HS307 and HS408, on human Xq21.…”
Section: Resultsmentioning
confidence: 96%
“…According to the retrovirus hypothesis, recently proliferated retroviral elements in the human genome after separation of the human and chimpanzee could be implicated with the psychotic diseases (Crow, 1984). In the previous study, we identified two retroposons (HS307 and HS408) and four HERV-K LTRs (K-X7-3, K-X10-5, K-X13-1, and K-X13-2) in human Xq21.3 region by PCR approach using YAC clone panel (Kim et al, 1999b;Kim and Crow, 2001), as the Xq21.3 region has been known to be putativefy linked to psychosis (Laval et al, 1998).…”
Section: Resultsmentioning
confidence: 99%